2022
DOI: 10.3390/nu14163441
|View full text |Cite
|
Sign up to set email alerts
|

Early Enteral Nutrition in Paediatric Acute Pancreatitis—A Review of Published Studies

Abstract: Nowadays, nutrition is said to be an integral aspect of acute pancreatitis (AP) treatment. Early enteral nutrition (EEN) is safe and beneficial for patients. This was confirmed by clinical experience and can be found in guidelines on managing adults with AP. Furthermore, paediatric recommendations encourage EEN use in AP. However, paediatric guidelines are based exclusively on studies in adults. Therefore, we present a review of published studies on the time of nutritional interventions in children with AP. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…Additionally, an encompassing meta-analysis highlighted that EEF within the initial 48 hours of admission exhibited enhanced clinical outcomes for acute pancreatitis by mitigating complications [ 5 ]. Moreover, an examination of published studies about pediatric acute pancreatitis concurred, indicating a positive association between EEF and improved clinical outcomes [ 6 ]. Collectively, these findings robustly support the potential benefits of EEF in managing acute pancreatitis.…”
Section: Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, an encompassing meta-analysis highlighted that EEF within the initial 48 hours of admission exhibited enhanced clinical outcomes for acute pancreatitis by mitigating complications [ 5 ]. Moreover, an examination of published studies about pediatric acute pancreatitis concurred, indicating a positive association between EEF and improved clinical outcomes [ 6 ]. Collectively, these findings robustly support the potential benefits of EEF in managing acute pancreatitis.…”
Section: Reviewmentioning
confidence: 99%
“…The review also underscored the comparable safety profiles of nasogastric and nasojejunal routes [ 3 ]. A randomized controlled trial focusing on pediatric acute pancreatitis patients demonstrated that the implementation of EEN, coupled with aggressive fluid resuscitation, significantly contributed to improved clinical outcomes [ 6 ]. A Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA)-compliant systematic review and meta-analysis comparing EEN with delayed enteral nutrition (DEN) in acute pancreatitis indicated a lower incidence of complications associated with EEN [ 8 ].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations